The Relationship between Parenting Patterns and Fish Consumption in Elementary School-Age Children in West Aceh District - Wardah Iskandar, SKM, M.Ph; Sri Wahyuni Muhsin; Sukma Elida; Hanif Muchdatul Ayunda (Universitas Teuku Umar, 2021)
Seafood is a nutrient-dense food that is needed by children in their infancy. Sea fish is rich in protein, vitamins and minerals as well as omega 3 fatty acids which are very important for the growth of both body cells and brain cells. Several factors are identified as the cause of low fish consumption in Indonesia, among others, the lack of public understanding of nutrition and the benefits of fish consumption for health and intelligence, socio-economy and culture. So that it affects the parenting style of parents in providing food intake to children. The large protein content in fish is expected to be able to improve the nutritional needs of the Indonesian people and the increase in fish consumption is also expected to have an effect on increasing the intelligence of the Indonesian people. The research aimed to determine the relationship between parenting and fish consumption among school-age children in Aceh Barat District. This study was a cross-sectional study. The sample in this study amounted to 173 elementary school age children in grades IV and V. The data was collected by means of direct interviews which included the patterns of upbringing and fish consumption. Data analysis includes univariate and bivariate analysis with independent sample t-test. From 173 children, it was found that 80.3% of children consumed fish well, while only 19.7% of children with poor fish consumption. Maternal parenting affects children's fish consumption with an OR = 12.865 (95% CI 4.933-3.552) so that maternal parenting has a 12.86 times chance of influencing fish consumption in children.